Defects of Tourism Revenue Sharing Policies and Practices in East Africa - Tumusiime, David Mwesigye; Byakagaba, Patrick (Advances in Social Sciences Research Journal, 2019)
Sharing of tourism revenues with local communities has for long been regarded as a key instrument in the arsenal for contemporary conservation. The approach is favored for its ability to simultaneously deliver both conservation and rural development moreover in mutually reinforcing ways. This paper reviews literature covering the practice at Protected Areas (PAs) in East Africa and a number of critical inadequacies are revealed. These include the marginal scale of benefits as observed in an evaluation of a regional project where per capita investment averaged only $ 0.36 over a five year period (2006-2010). Moreover, these revenues are frequently invested in public assets (e.g. schools and roads) which communities have limited appreciation of on the argument that these should be primary responsibilities of national and local governments to whose coffers the communities contribute through taxation. Even when individual households are targeted through household level projects, the sharing is plagued by a variety of governance failures including elite capture, and distributive inequity where for example the poor (the lower two to three quintiles) tend to be excluded. Inequity also exists at community level where some local administrative units are marginalized, and in other instances the revenues are used to reward loyalty while also there is a significant leakage of revenues along the vertical distribution chain of local government implementing the revenue sharing. Thus a lot remains to be done if these schemes for sharing tourism revenues are to deliver as premised. There is need to substantially increase the magnitude of the local share which then must be secured by competent and legitimate, but closely supervised, local institutions to ensure equitable distribution between and within local communities.